Effect of Artificial Vegetation on Wave Attenuation – An Experimental Investigation. (2015) - John, Beena Mary; Shirlal, Kiran G.; Rao, Subba
Abstract: In the wake of threats posed by rising sea levels and increasing severity of storms, the use of soft measures in coastal protection is acquiring an ever increasing importance. Coastal vegetation acts as a complex interface ecosystem between human communities and the sea and provides important ecosystem services by protecting these communities from coastal hazards, providing critical habitat for fishes and marine invertebrates and primary food source for animals like sea turtles. This paper tries to bring out the effect of simulated vegetation on wave attenuation through an experimental study. The tests were carried out with submerged artificial seagrass and artificial rigid vegetation in a 50 m long wave flume. For wave heights ranging from 0.08 m to 0.16 m at an interval of 0.02 m and wave periods 1.8 s and 2 s in water depths of 0.40 m and 0.45 m, measurements of wave heights at locations along the vegetation were observed.